ANALYSIS OF DEIXIS IN THE SUBTITLE MOVIE OF â€œFIRST KISSâ€ - Fitria, Tira Nur (English Department of Faculty of Tarbiyah and Teacher Training, 2020)
The objective of this research is to analyze the type and its examples of deixis found in the subtitle movie of ?First Kiss?. This research method of this method is qualitative methodology. In data collection, the research use document analysis in this research. The result of this research shows that three types of deixis found in the subtitle movie of ?First Kiss? movie such as a person, time, and place deixis. In-person deixis, the deictic expressions are the personal pronoun ?I? as a singular subject pronoun, ?Me? as singular object pronoun, ?My? as a possessive adjective, ?We? as a plural subject pronoun, ?Us? as object pronoun, ?Our? as a possessive adjective. In the second person, they are ?You? as a subject and object pronoun, and ?Your? as an object pronoun. The third person ?He? as a subject pronoun, ?Him? as object pronoun, and ?His? as a possessive adjective, ?She? as a subject pronoun, ?Her? as object pronoun and as possessive adjective, ?It? as subject and object pronoun. In space/spatial/place deixis, the deictic expressions are ?here? and ?there?. While in the temporal/time deixis, the deictic expressions are ?now? and ?tomorrow?.